1992
DOI: 10.1021/ac00047a004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tyrosine on the dual electrode electrochemical detection of copper(II)-peptide complexes

Abstract: The bluret reaction makes peptides electrochemically active. This is the basis of an electrochemical method for the detection of peptides following their liquid chromatographic separation. This paper discusses the influence of tyrosine, an electroactive amino acid, on the detection of Cu(II)-peptide (bluret) complexes containing it. The dual electrode detector has an upstream anode and a downstream cathode. Tyrosine-containing peptides yield anodic signals that are approximately the sum of the tyrosine signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 14 publications
2
43
0
Order By: Relevance
“…The biuret reaction and LC-EC has been extensively investigated for the sensitive and selective determination of peptides [12][13][14][15][16][17][18][19][20]. The reaction conditions for complex formation had previously been investigated by both Margerum and co-workers [21][22][23][24] and Weber's group [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biuret reaction and LC-EC has been extensively investigated for the sensitive and selective determination of peptides [12][13][14][15][16][17][18][19][20]. The reaction conditions for complex formation had previously been investigated by both Margerum and co-workers [21][22][23][24] and Weber's group [25].…”
Section: Introductionmentioning
confidence: 99%
“…Most work using the biuret reaction has relied on preor postcolumn derivatization of peptides with copper to form copper-peptide complexes [12][13][14][15][18][19][20]. Recently, our group has shown that complexes could be formed on-capillary [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…4). The Tyr-containing peptide copper complex provides a considerably greater electrochemical response than does the non Tyr-containing peptide copper complex, as expected [13,25]. However, the significant difference in E max illustrates the possibility for tunable selectivity with electrochemical detection.…”
Section: On-capillary Complexation and Detection Of A Nonelectroactivmentioning
confidence: 70%
“…The increase in sensitivity and lower LOD are due to a combination of factors. The anodic signal generated from the oxidation of the copper complex is an additive effect from the Tyr and Cu(II) oxidation [13]. The position of Tyr in the peptide also affects the electrochemical signal.…”
Section: Plasma Analysismentioning
confidence: 99%
See 1 more Smart Citation